AGRICULTURE PRODUCTION TYPOLOGY OF KHARKIV REGION: AFTER THIRTY YEARS - Сонько, Сергій (Human Geography Journal, 2016)
Attention on the large value of agriculture geography is accented in forming of subject field of society geography. With the use of author method elementary GIS typology of agricultural enterprises of the Kharkov area is executed. At comparing of modern production types to those, that formed 30 years ago the main geographical conformities are setting.